Beyond Chemical Triggers: Evidence for Sound-Evoked Physiological Reactions in Plants - Jung, Jihye; Kim, Seon-Kyu; Kim, Joo Y.; Jeong, Mi-Jeong; Ryu, Choong-Min (Frontiers in Plant Science, 2018)
Sound is ubiquitous in nature. Recent evidence supports the notion that naturally occurring and artificially generated sound waves contribute to plant robustness. New information is emerging about the responses of plants to sound and the associated downstream signaling pathways. Here, beyond chemical triggers which can improve plant health by enhancing plant growth and resistance, we provide an overview of the latest findings, limitations, and potential applications of sound wave treatment as a physical trigger to modulate physiological traits and to confer an adaptive advantage in plants. We believe that sound wave treatment is a new trigger to help protect plants against unfavorable conditions and to maintain plant fitness.